(untitled) (AYUSHDHARA, 2022)
Human community is in agony of grave metabolic disorder i.e., obesity/Sthaulya roga. It is inclined to become miserable because of the attenuated Dosha in the body. Sedentary lifestyle, hampered sexual life, extreme lassitude, will be prone to engulf the normalcy of an individual, which ultimately leads to decreased life span. It is widely recognized that obesity has emerged as an epidemic in developed nations. It continues to be an issue of great concern. In addition, we now face the emergence of obesity as a worldwide phenomenon, affecting affluent and ordinary group of class. Here in this case report the objective is to find out the efficacy of Vrikshamla (Garcinia Cambogia) in the management of Sthaulya (Obesity). Materials: A 32 years old male patient K/C/O obesity since three year. Accustomed him with sedentary lifestyle which leads to an drastic gain in the weight. Through physical findings, BMI of a patient is 32.3 and by investigations the diagnosis led to Sthaulya as well as dyslipidemia. The study was assessed by both subjective and objective criteria. The treatment plan opted was Ayurveda internal medicine “Vrikshamla are best in the management of Sthaulya, selected as per criteria and examined by means of Roga and Rogi Pariksha methods. Administered Vrikshamla 2gm per day for 60 days and subjective as well as objective parameters were Assessed based on before and after treatment. Discussion: Difference in the values of subjective and objective parameters, illustrate all the clinical observations in respect of incidences of Nidana, Lakshana and percentage of relief in the subject. Conclusion: In the present research work undertaken, Vrikshamla an herbal formulation prove its efficacy against dyslipidaemia.